Nonsense Mutation Inside Anthocyanidin Synthase Gene Controls Pigmentation in Yellow Raspberry (Rubus idaeus L.) - Rafique, Muhammad Z.; Carvalho, Elisabete; Stracke, Ralf; Palmieri, Luisa; Herrera, Lorena; Feller, Antje; Malnoy, Mickael; Martens, Stefan (Frontiers in Plant Science, 2016)
Yellow raspberry fruits have reduced anthocyanin contents and offer unique possibility to study the genetics of pigment biosynthesis in this important soft fruit. Anthocyanidin synthase catalyzes the conversion of leucoanthocyanidin to anthocyanidin, a key committed step in biosynthesis of anthocyanins. Molecular analysis of the Ans gene enabled to identify an inactive ans allele in a yellow fruit raspberry (“Anne”). A 5-bp insertion in the coding region was identified and designated as ans+5. The insertion creates a premature stop codon resulting in a truncated protein of 264 amino acids, compared to 414 amino acids wild type ANS protein. This mutation leads to loss of function of the encoded protein that might also result in transcriptional downregulation of Ans gene as a secondary effect i.e. nonsense-mRNA mediated decay. Further, this mutation results in loss of visible and detectable anthocyanin pigments. Functional characterization of raspberry Ans/ans alleles via complementation experiments in the Arabidopsis thaliana ldox mutant supports the inactivity of encoded protein through ans+5 and explains the proposed block in the anthocyanin biosynthetic pathway in raspberry. Taken together, our data shows that the mutation inside Ans gene in raspberry is responsible for yellow fruit phenotypes.